Effects of binary stellar populations on direct collapse black hole formation - Agarwal, Bhaskar; Klessen, Ralf S.; Glover, Simon (Monthly notices of the Royal Astronomical Society. Letters, 2017)
The critical Lyman-Werner (LW) flux required for direct collapse blackholes (DCBH) formation, or Jcrit, depends on the shape of the irradiating spectral energy distribution (SED). The SEDs employed thus far have been representative of realistic single stellar populations. We study the effect of binary stellar populations on the formation of DCBH, as a result of their contribution to the LW radiation field. Although binary populations with ages > 10 Myr yield a larger LW photon output, we find that the corresponding values of Jcrit can be up to 100 times higher than single stellar populations. We attribute this to the shape of the binary SEDs as they produce a sub-critical rate of H− photodetaching 0.76 eV photons as compared to single stellar populations, reaffirming the role that H− plays in DCBH formation. This further corroborates the idea that DCBH formation is better understood in terms of a critical region in the H2-H− photodestruction rate parameter space, rather than a single value of LW flux.